Análise de confiabilidade estrutural com expansão polinomial - Medeiros, Eduardo Morais de (2018)
All engineering structures must accomplish a series of requisites and criteria, which may be related to structural safety, and some admissible deformations that may cause discomfort and insecurity. Moreover, the structure's response to external forces depends on its cross section, its materials properties, the type and intensity of the loads and other factors. One of the ways of assessing these criteria and structural safety is evaluating the probability of failure. In general, the evaluation of the probability of structural failure generates a significant computational cost. Therefore, aiming to reduce the computational effort and maintaining the efficiency of the obtained results, the proposal of this study is to use the polynomial expansion in structural realiability analysis. For this purpose, the original functions are replaced by polynomials, resulting in a accurate analysis with low computational cost. Thus, numerical applications for truss and beam structures are presented and the results obtained show the effectiveness of the proposed formulation.